Linear Scleroderma and Neurological Complications - J Gordon Millichap (Pediatric Neurology Briefs)
Three patients with linear scleroderma en coup de sabre who presented with neurologic abnormalities before or concurrent with the dermatologic diagnosis are reported from the Medical College of Wisconsin, Milwaukee, WI.